Current research and future prospects of immunonutrition in gastrointestinal malignancies - Ma, Xiaoyan; Pei, Beibei; Wu, Na; Wang, Chen; Yu, Yanling; Yang, Wenhui (Frontiers in Immunology, 2024)
Immune nutrition, as an integral component of nutritional support therapy, has garnered significant attention and research in the treatment of gastrointestinal malignancies. Recent advancements in nutritional formulas containing components such as glutamine, omega-3 polyunsaturated fatty acids, and arginine have led to the development of what is now termed immune nutrition or pharmacological nutrition. These formulations go beyond traditional nutritional support, functioning more like nutritional supplements with pharmacological effects. Patients with gastrointestinal malignancies often experience malnutrition and metabolic disturbances, resulting in immune dysfunction, cytokine dysregulation, and endocrine abnormalities. These issues can compromise intestinal mucosal barrier function, affecting the efficacy and prognosis of anticancer therapies.Recent studies indicate that immune nutrition can modulate specific mechanisms involved in various immune and inflammatory pathways, thereby improving patients' immune status and treatment outcomes. While optimal patient selection, dosing, and timing of immune nutrition are still under investigation, its potential applications in oncology are promising. This article aims to analyze the existing evidence regarding the therapeutic benefits of immune nutrition in gastrointestinal malignancies, offering insights into its clinical standardization and application.